Karakterisasi Kimiawi Tepung Sereal Terfermentasi oleh Bakteri Asam Laktat dan Saccharomyces Cereviceae - Putri, Widya Dwi Rukmi; Zubaidah, Elok; Saparianti, Ella; P.S., Monika Maria (Jurnal Teknologi Pertanian, 2003)
Cereal and legume based product have low digestion because consist of complex component that hard to digest. Fermentation cereal by microbe can improve this condition. This research aims to know the effect of fermentation instant cereal by Lactic Acid Bacteria and Saccharomyces cereviceae. The result showed decreasing starch concentration, increasing total acid and N-amino concentration. Keyword: fermentation, cereal